Bilobed Thoracic Meningomyelocele: A Case Report with Literature Review - Shrestha, Dipendra; Rajbhandari, Binod; Shilpakar, Sushil Krishna (Nepal Journal of Neuroscience, 2019)
Neural tube defects (NTDs) arethe most common congenital malformations affecting the brain and spinal cord. Furthermore, meningomyelocele (MMC) is said to be one of the commonest NTDs. Multiple MMC is uncommon and bilobed sac is even rarer, comparatively. In literature, only few such cases have been reported. Here, we present a rare case of bilobed thoracic MMC operated successfully in our department.